Innovation of Natural Preservation of Mackerel (Rastrelliger kanagurta) Using Coconut Coconut Ashes with Drying Time Variations on Hedonics - Rika Agustina; Rita Sunartaty; Teuku Makmur; Ruka Yulia (Universitas Serambi Mekkah, 2020)
Coconut frond ash is one of the wastes from coconut trees which has not been maximally utilized. Coconut frond ash contains MgCl2 and KCl so that it can be used as a salt substitute in the process of preserving fish. In this study coconut frond ash was used as a basic ingredient for making dried mackerel with a long time of drying to storage. The purpose of this study was to determine the effect of drying time on mackerel storage. The research design used was a Randomized Block Design (RCBD) with 2 factors studied. The first factor is the drying time consists of 3 levels, namely P1 = 3 days, P2 = 4 days, P3 = 5 days. The second factor is storage which consists of 3 levels, namely S1 = 30 days, S2 = 60 days, S3 = 90 days. Each treatment was repeated 2 times to obtain 18 experimental units to observed hedonic tests. From the results of the study it can be stated that the treatment has a very significant effect (P≥0.01) on the hedonic test which includes (color, aroma, taste and texture).